A Review on Microbial Coal Biodegradation for Methane Production - He, Haodong (International Journal of Natural Resources and Environmental Studies, 2026)
Coal biomethanation, as a green and low-carbon energy conversion technology, has shown significant application potential in coalbed methane (CBM) development. This paper systematically reviews the mechanisms and research progress of microbial coal biodegradation for methane production. The key processes, including hydrolysis, fermentation, hydrogen-producing acetogenesis, and methanogenesis, as well as their synergistic microbial interactions, are analyzed in detail. The characteristics of microbial community structures in coal seams are summarized, revealing that methane generation generally follows a metabolic pattern of “bacterial primary degradation coupled with archaeal terminal methanogenesis,” with hydrogenotrophic methanogens dominating in most basins. Furthermore, the progress of mixed microbial cultures combining indigenous and exogenous microorganisms for enhancing coal biogasification is reviewed. It is indicated that multi-source microbial consortia exhibit significant functional complementarity; however, their performance is influenced by factors such as community structure, environmental conditions, and interspecies interactions. Finally, current limitations in degradation mechanisms, functional microbial identification, and system stability are discussed, and future research directions are proposed, emphasizing the need for deeper mechanistic insights and microbial regulation strategies to promote the engineering application of coal biomethanation.